Professor Mack A. Breazeale - ŚLIWIŃSKI, Antoni (Archives of Acoustics, 2009)
Dr Mack A. Breazeale - retired Distinguished Research Professor and Senior Scientist in the National Center for Physical Acoustics at the University of Mississippi, Member of the Advisory Editorial Board of Archives of Acoustics, passed away at his home in Oxford - Mississippi, USA on 14th September 2009.